2023
DOI: 10.1021/acs.macromol.3c00214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Norbornene Anchor Group in Ru-Mediated Ring-Opening Metathesis Polymerization: Synthesis of Bottlebrush Polymers

Abstract: Ring-opening metathesis polymerization (ROMP) mediated by Grubbs’ third-generation catalyst [G3, (H2IMes)(Cl)2(pyr)2RuCHPh] is widely used to make bottlebrush polymers by polymerization of a macromonomer (MM), typically a low molecular weight polymer functionalized with a norbornene. Termed the grafting-through method, this strategy requires a high degree of living character (“livingness”) to form well-defined bottlebrush polymers. Here, we studied how various anchor groups, the series of atoms connecting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…We attribute this to an apparent influence of the degree of polymerization on k p , where k p decreases at high conversion due to the steric demands of the growing bottlebrush macromolecule, a phenomenon we have observed previously. 49 Additionally, instead of reaching complete conversion, both MMs leveled off at 95% conversion based on SEC, even though 1 H NMR spectroscopy confirmed complete (>99%) consumption of the norbornene in all three cases. This phenomenon was previously observed in other norbornene MMs made by ATRP and is attributed to the presence of ∼5% MM species that lack a norbornene end group.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We attribute this to an apparent influence of the degree of polymerization on k p , where k p decreases at high conversion due to the steric demands of the growing bottlebrush macromolecule, a phenomenon we have observed previously. 49 Additionally, instead of reaching complete conversion, both MMs leveled off at 95% conversion based on SEC, even though 1 H NMR spectroscopy confirmed complete (>99%) consumption of the norbornene in all three cases. This phenomenon was previously observed in other norbornene MMs made by ATRP and is attributed to the presence of ∼5% MM species that lack a norbornene end group.…”
Section: Resultsmentioning
confidence: 90%
“…25,46,47 Our group has studied the effects of the anchor group in ROMP, and we have found that the energy of the HOMO centered on the norbornene olefin of various (macro)monomer structures is a reasonable predictor for olefin reactivity, showing a positive correlation with k p values. 48,49 Therefore, development and characterization of new anchor groups broadens the scope of bottlebrush polymer materials by increasing (macro)monomer structural diversity and allowing for tunability of monomer olefin reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…When synthesizing more complex topologies by ROMP, i.e., bottlebrush polymers, choice of anchor group becomes critical to reach high degrees of polymerization and achieve low dispersity polymers. A companion paper to this one focuses on this topic …”
Section: Discussionmentioning
confidence: 99%
“…Chemists have established precise polymerization techniques to create polymers with complex topologies that resemble macroscopic architectures found in nature . Such complex polymer topologies are not merely academic curiosities; polymers with sophisticated and distinct structures allow for creating materials with specialized properties and functionalities. , In particular, the bottlebrush polymer architecture, which contains a linear backbone with densely grafted polymeric side chains (Figure , left), provides exceptional potential for controlling polymer structure and properties by modifying the composition and degree of polymerization of the backbone and side chains ( N bb and N sc , respectively). Recently, our group and others have added a new dimension to bottlebrush polymer synthesis by systematically varying the molecular weight of the side chains along the backbone to create nanoscale cones termed tapered bottlebrush polymers (Figure , right). Cone-shaped structures appear in nature, for example, in the HIV viral envelope and in the protein assemblies that form the tobacco mosaic virus. , Cone-shaped materials and other noncentrosymmetric structures have also been the center of experimental and computational investigations of self-assembled nanostructures that mimic naturally occurring molecular architectures or that readily integrate into biological materials.…”
Section: Introductionmentioning
confidence: 99%